Tuberculosis in Mexico and the USA, Comparison of Trends Over Time 1990-2010 - Hernández-Garduño, Eduardo (Tuberc Respir Dis (Seoul), 2015)
BACKGROUND: The aim was to compare tuberculosis trends in Mexico and United States and to evaluate Mexican diagnostic methods and contact investigation. METHODS: Retrospective comparative study of tuberculosis cases and incidence rates between both countries (1990-2010). Diagnostic methods and contact investigations were also evaluated for Mexico. Estimates were obtained from official websites. RESULTS: In Mexico, no clear trend was found over time for cases. Pulmonary (PTB) and all forms of tuberculosis (AFTB) incidence decreased 2.0% annually. There was a negative correlation between the mean contacts examined per case and AFTB incidence (r(2)=-0.44, p=0.01) with a 33% reduction in AFTB incidence. In United States, PTB and AFTB cases have been decreasing 6.0% and 5.6% annually, respectively. The incidence decreased 7.3% and 6.8%, respectively. CONCLUSION: The incidence of tuberculosis in Mexico is decreasing slightly over time at 2% annually. In the United States, cases and incidence rates have been decreasing at a higher rate (5% to 7% annually). The inverse association between number of contacts examined per state and incidence rates in Mexico underscore the importance of reinforcing and improving contact investigations with the likely translation of a decrease of TB incidence at a higher rate.